Implicit Attitudes Toward Psychotherapy and Explicit Barriers to Accessing Psychotherapy in Youths and Parent–Youth Dyads - Simone Pfeiffer; Ashley Huffer; Anna Feil; Tina In-Albon (Clinical Psychology in Europe, 2022)
[Background] Few studies have investigated implicit and explicit attitudes toward psychotherapy in youths (Study 1), although information about attitudes would improve interventions that aim to decrease barriers to accessing psychotherapy including parents (Study 2), who facilitate the help-seeking process of youths. [Method] The Study 1 sample comprised 96 youths (14–21 years) and the Study 2 sample 38 parent–youth dyads. Differences in implicit attitudes regarding psychotherapy and a medical treatment were measured with the Implicit Association Test, and psychotherapy knowledge and self-reported barriers to psychotherapy were assessed with questionnaires. The actor-partner interdependence model was used to test the dyadic effects of implicit attitudes on explicit attitudes in parents and youths. [Results] We did not find evidence for an implicit bias toward psychotherapy compared to a medical treatment, neither in youths, nor in parents. Self-reported barriers were a predictor for lower help-seeking intentions. Deficits in psychotherapy knowledge were more relevant in younger participants. Having a prior or current experience with psychotherapy and having a friend or family member with a prior or current experience with psychotherapy were predictors for better psychotherapy knowledge, but was not for lower barriers to accessing psychotherapy. Partner effects (degree to which the individual’s implicit attitudes are associated with explicit attitudes of the other dyad’s member) were not found. [Conclusion] Specific deficits in psychotherapy knowledge should be addressed in interventions to lower barriers accessing psychotherapy. Parents should be included in interventions as a valuable resource to support youths in seeking psychotherapy for mental disorders.